Neo-Eurasianism in Russian Foreign Policy: Echoes from the Past or Compromise with the Future? - Aryanta Nugraha (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2015)
With its growing geopolitical inclination, Russian foreign policy has beenconsidered as a resurgence of Eurasianism (Neo-Eurasianism).Notwithstanding its strong geopolitical sense, Eurasianism is multifacetedconcept. It is often associated with philosophical thinking, cultural andpolitical doctrines which changed over time and yet full of contradictions. Thisarticle seeks to find out the influence of Neo-Eurasianism in Russian foreignpolicy. Tracing back the idea of Eurasianism from historical perspective andemploying Graham Smith classification on school of Eurasianism, this articleargues that the rise of Neo-Eurasianism in Russia is driven by the needs todefine and strengthen the spheres of influences. It is mainly motivated byethnocentric sentiments to expand the sphere of influences across the border as a safeguard and protection. Neo-Eurasianism compromises building aforeign policy consensus based on political culture and national awareness.